COVID-19 and African Firms : Impact and Coping Strategies - Aga, Gemechu (World Bank, Washington, DC, 2021)
Drawing on a representative survey of firms in 38 countries, eight of which are in Sub-Saharan Africa, this paper documents the impact of COVID-19 and firms’ coping strategies in Sub-Saharan Africa, benchmarking with other regions. The paper shows that the impact of the pandemic is more pronounced in Sub-Saharan Africa compared with other regions. This disproportionate impact is not explained by differences in sectoral composition and other firm characteristics, but likely by the level of development. This underscores the important economic and structural contexts that predate the pandemic in understanding the differential impact. Contrary to expectations, the findings show that businesses in Sub-Saharan Africa are more likely to adjust their operations or products and services to adapt to the shock than those in other regions. However, firms in the region lag in leveraging digital technologies, remote working, and e-commerce, compared with those in other regions.